On-line gaming : its effects to grade 11 learners of public senior high schools - Lomboy, Darius Seymon G. (Agoo, La Union : [s.n.], 2017)
The study assessed the effects of on-line games to grade 11 learners in the public senior high schools of Aringay District, Division of La Union during the school year 2016-2017. Majority of the learners are 16 years old female whose parents are high school graduates and earning a family monthly income of P5,001-P10,000. There was a great extent of the causes of on-line gaming to Grade 11 learners of public senior high schools of Aringay District, Division of La Union. Grade 11 learners moderately preferred on-line games. There was a great extent of the positive and negative effects of on-line gaming. The problems encountered relative to the on-line gaming were perceived to be moderately serious. MEasures to address these problems encountered were perceived to be highly applicable.
Bibliography: pages 64-65.
CHED-La Union
Keywords: Computer games